成纤维细胞生长因子受体样蛋白1在口腔鳞状细胞癌中的表达及其对细胞增殖和迁移能力的影响 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2020)
OBJECTIVE: This study aims to investigate the expression of fibroblast growth factor receptor like 1 (FGFRL1) in oral squamous cell carcinoma (OSCC) and reveals its association with tumor cell proliferation and migration. METHODS: Western blot was performed to detect the expression of FGFRL1 protein in OSCC tissues, adjacent normal tissues, OSCC cell lines and normal epithelial cells. After knocking down of FGFRL1 in HN4 cells, CCK-8 and Ki67 assays were performed to detect cell proliferation, wounding healing assay and transwell were performed to detect cell-migration. Western blot was used to detect the expression of protein related to epithelial-mesenchymal transition (EMT). RESULTS: The expression of FGFRL1 in OSCC tissues was higher than that in adjacent nontumor tissues, respectively (t=2.820, P=0.047 8). Moreover, the expression of FGFRL1 in OSCC cells was higher than that in HOK cells. Quantitative real-time polymerase chain reaction (qRT-PCR) showed that FGFRL1 expression of FGFRL1 RNA in HOK cells was lower than that in OSCC cells. HN4 cells transfected with FGFRL1 siRNA were included in the experimental group, whereas HN4 cells treated with NC siRNA were included in the control group. CCK-8 experiment showed no significant difference between the experimental and control groups with regard to proliferation ability at 48 h (P=0.478 1) and 72 h (P=0.334 2). Migration experiment showed that the wound healing areas in the experimental group after 12 h (P=0.022 8), 24 h (P=0.005 1), and 36 h (P=0.009 5) were smaller than that in the control group. Transwell invasion assay showed that the number of invaded cells in the experimental group after 16 h (P=0.008 7) and 24 h (P=0.008 6) were lower than that in the control group. Knocking-down FGFRL1 up-regulated the expression of E-cadherin and down-regulated the expression of N-cadherin and Vimentin in HN4 cells. CONCLUSION: FGFRL1 expression in the OSCC tissues was significantly higher than that in the adjacent nontumor tissues. FGFRL1 expression in the OSCC cells was significantly higher than that in the HOK cells, and FGFRL1 had no effect on cell proliferation but promoted tumor cell migration and EMT.